Shock Wave Propagation Characteristics of Cylindrical Charge and Its Aspect Ratio Effects on the Damage of RC Slabs - Xiaohua Zhao; Gaohui Wang; Hongyuan Fang; Yong Fan; Xueming Du (Advances in Materials Science and Engineering)
Antiknock research of reinforced concrete (RC) slabs is often carried out with spherical or nearly spherical explosives, although many explosives used in engineering and military are cylinder shaped. It is known that the shock wave caused by cylindrical explosives varies in different directions, which is quite different from the spherical charge. In this paper, the shock wave propagation characteristics of spherical and cylindrical explosives with different aspect ratios are compared and analyzed. The 2D numerical results show the peak overpressure from the cylindrical explosive is significantly affected by the L/D (length/diameter) ratio. Subsequently, the damage features of RC slabs under spherical and cylindrical explosives with a certain L/D ratio are investigated through an explosion experiment. Finally, the influence of the L/D ratio on the dynamic response of RC slabs under cylindrical explosives is studied by the fully coupled Euler–Lagrange method. The accuracy and reliability of the coupled model are verified by comparing the numerical with experimental results. Based on the experimental and numerical studies, it can be concluded that the explosive shape directly determines the shape of upper surface crater damage, and the spall damage area of RC slabs becomes larger as the L/D increases. For the L/D increases to a certain value, the cylindrical explosive will induce larger spall damage than that induced by spherical charge with the same amount of explosives. Hence, the effect of the cylindrical charge should be considered in the antiknock design of the RC structure.